Differentiated curriculum and instruction for advanced and gifted learners - Kaplan, Sandra Nina (Routledge, Taylor & Francis Group, 2022)
This critical volume provides readers with a deep understanding ofwhyandhowto differentiate curriculum and instruction to better meet the academic, social, and emotional needs of advanced and gifted learners. Offering clear, constructure frameworks for learning, chapters focus on four key concepts - review, reinforce, refine, and redefine - which help readers create individualized learning experiences and differentiate standards-based curriculums. Filled with specific examples, lessons, and units of study, this essential guide emphasizes differentiation as a means to differ the What (curriculum) as well as the How (instruction) to successfully respond to the many facets of students' giftedness.